2022
DOI: 10.3389/fnins.2022.960026
|View full text |Cite
|
Sign up to set email alerts
|

Benign regulation of the gut microbiota: The possible mechanism through which the beneficial effects of manual acupuncture on cognitive ability and intestinal mucosal barrier function occur in APP/PS1 mice

Abstract: BackgroundGut microbiota dysbiosis and intestinal barrier injury play vital roles in Alzheimer’s disease (AD) onset and development. Our previous studies have demonstrated that manual acupuncture (MA) could improve the cognitive abilities of APP/PS1 mice. However, the effect of MA on the intestinal mucosal barrier and the gut microbiota mechanism through which this effect occurs remain to be clarified.MethodsIn the APP/PS1 manual acupuncture (Am) group, MA was applied in Baihui (GV20), Yintang (GV29), and Zusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…EA was protective against the deleterious metabolic changes caused by high-fat diet-induced obesity via modulating the gut microbiota ( 60 ). MA mitigated the gut microbiota changes in the APP/PS1 Alzheimer's disease mouse group, and the cognitive function and the intestinal barriers were also improved in the MA treatment group ( 61 ). The gut microbiota is another potential platform to explain the crosstalk between the immune system and the neural system.…”
Section: Discussionmentioning
confidence: 99%
“…EA was protective against the deleterious metabolic changes caused by high-fat diet-induced obesity via modulating the gut microbiota ( 60 ). MA mitigated the gut microbiota changes in the APP/PS1 Alzheimer's disease mouse group, and the cognitive function and the intestinal barriers were also improved in the MA treatment group ( 61 ). The gut microbiota is another potential platform to explain the crosstalk between the immune system and the neural system.…”
Section: Discussionmentioning
confidence: 99%
“…International research on traditional Chinese medicine for the treatment of AD has focused on Chinese herbs [e.g., Morinda officinalis How , Astragali radix (Dong et al, 2022)] or active ingredients of Chinese herbs [e.g., polysaccharides , ginsenoside (Wu et al, 2022a), evodiamine (Pang et al, 2022), Huperzine A (Yan et al, 2022)], herbal prescriptions [e.g., Yi-Gan San (Yang et al, 2023), Yuan-Zhi Decoction (Wu et al, 2022b)], special therapies [e.g., Wuqinxi exercise (Luo et al, 2022), Tai Chi Quan (Wang et al, 2022)], and acupuncture (Cai et al, 2019;Yu et al, 2021a;Zheng et al, 2021;Hao et al, 2022) to improve memory and cognitive impairment in AD models, involving various mechanisms such as regulation of βamyloid and tau proteins, anti-oxidation, anti-neuroinflammation, modulation of autophagy and many other mechanisms. Among these, acupuncture is considered to be a highly promising alternative therapy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…In diseased animals, Hao et al (2022) observed under an electron microscope that the damage of small intestine structures were significantly reduced after intervention with manual acupuncture. An electron-microscopical examination reveals a mild separation of the epithelium from the lamina propria, an orderly arrangement of intestinal gaps as well as narrower connection gaps.…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 98%
“…According to Hao et al (2022) , mice experiencing manual acupuncture showed a significant increase in Bacteroides while a decrease in Proteobacteria and Escherichia–Shigella, however, no significant improvement in intestinal microbiota diversity was found, perhaps method of calculating diversity or insufficient samples might limit the result of diversity.…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 99%
See 1 more Smart Citation